Metal chloride cathodes for next-generation rechargeable lithium batteries - Yiming Dai; Shuoqing Zhang; Jiayun Wen; Zhenyou Song; Tengrui Wang; Renyuan Zhang; Xiulin Fan; Wei Luo (iScience, 2024)
Summary: Rechargeable lithium-ion batteries (LIBs) have prospered a rechargeable world, predominantly relying on various metal oxide cathode materials for their abilities to reversibly de-/intercalate lithium-ion, while also serving as lithium sources for batteries. Despite the success of metal oxide, issues including low energy density have raised doubts about their suitability for next-generation lithium batteries. This has sparked interest in metal chlorides, a neglected cathode material family. Metal chlorides show promise with factors like energy density, diffusion coefficient, and compressibility. Unfortunately, challenges like high solubility hamper their utilization. In this review, we highlight the opportunities for metal chlorides in the post-lithium-ion era. Subsequently, we summarize their dissolution challenges. Furthermore, we discuss recent advancements, encompassing liquid-state electrolyte engineering, solid-state electrolytes (SSEs) cooperation, and LiCl-based cathodes. Finally, we provide an outlook on future research directions of metal chlorides, emphasizing electrode fabrication, electrolyte design, the application of SSEs, and the exploration of conversion reactions.